2015
DOI: 10.1111/nep.12641
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of continuous erythropoietin receptor activator and darbepoetin Alfa treatments in Japanese patients with chronic kidney disease during the predialysis period: A propensity‐matched analysis

Abstract: Our study showed that CERA may be more effective than DA for management of anaemia during the predialysis period in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…5 Changes in hemoglobin (Hb) levels 1 year after initiation in the three groups according to the tertile of Hb levels and association between at initiation and 1 year after initiation. There were no significant differences in Hb at 1 year after initiation between the three groups, and there was no significant correlation between Hb at initiation and 1 year after initiation also reported the same correlation between them [9]. In our patients, there was a significant negative relationship between Hb and CTR at initiation.…”
Section: Discussionmentioning
confidence: 46%
“…5 Changes in hemoglobin (Hb) levels 1 year after initiation in the three groups according to the tertile of Hb levels and association between at initiation and 1 year after initiation. There were no significant differences in Hb at 1 year after initiation between the three groups, and there was no significant correlation between Hb at initiation and 1 year after initiation also reported the same correlation between them [9]. In our patients, there was a significant negative relationship between Hb and CTR at initiation.…”
Section: Discussionmentioning
confidence: 46%
“…Indeed, some previous studies used a dose conversion ratio of DA:CERA =1:0.93 for non-dialysis CKD patients, 13 whereas others used a ratio of 1:1. 23,24 We used a ratio of 1:1; however, even if a conversion ratio of 1:0.93 had been adopted, the conclusions of the present study would have remained the same.…”
Section: Discussionmentioning
confidence: 56%
“…23,24 Results of both of these studies showed a decline in Hb levels at the initiation of dialysis in CKD patients treated with epoetin, DA, or CERA. Each of these ESAs evidently failed to maintain target Hb levels at the initiation of dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study concluded that CERA could be more effective for correction of anemia in pre-dialysis patients. 22 The results of another study conducted in predialysis patients suggested no significant difference in the effects in regards to achievement of target hemoglobin levels in both groups ( Compliance is an important factor that determines the success of treatment and in this regards, patient's preference is considered as one of the important factors. Medicines which are preferred by the patients are more likely to be taken by them for longer period.…”
Section: Efficacy In Pre-dialysis Patientsmentioning
confidence: 99%